UPAYA OPTIMASI SISTEM PENGADAAN BARANG PERAWATAN UNTUK FASILITAS PRODUKSI DI DEPARTEMEN POWER, GAS, AND FACILITIES CNOOC SES LTD - , Subhan Alfajri ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The aim of this research is to figure out the supporting factors and also the obstacles in procurement strategyâs implementation in CNOOC SES Ltd. This evaluation is done by comparing supply activity for offshore equipment maintenance at Power, Gas, and Facilities Department, CNOOC.SES.Ltd in 2010 with the CNOOC.SES.Ltd standard procurement manual. This standard procurement manual is consist of spare partsâ price, spare partsâ delivery time, spare partsâ importance and frequency required in 1 year, which will be customized with the standard procurement strategy in CNOOC.SES.Ltd, specifically in Power, Gas, and Facilities Department. After we have the result, then we can provide alternatives and solutions to support more the procurement strategyâs implementation in the company.